1979
DOI: 10.1007/bf03189398
|View full text |Cite
|
Sign up to set email alerts
|

Serum kinetics of doxycycline polyphosphate in dogs

Abstract: Serum kinetics of Doxycycline polyphosphate (DPP) have been studied in dogs after oral administration of 10 mg.kg-1 by measurement of total serum concentration (Ct) of tetracycline derivatives by a chemical assay and active concentration (Ca) by a microbiological method. Kinetics have been studied using a one compartment open model with absorption by oral route. DPP is rapidly absorbed, the peak serum level is reached three hours after absorption and slowly eliminated (elimination half-life = 12 hours). The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Doxycycline is highly lipophilic and would be expected to be distributed widely in the chicken. Nevertheless, the V^m*) of 0.28 ± 0.02 I/kg determined in the present study was much lower than that reported for other species: 0.75 I/kg in adult humans (Raghuram & Krishnaswamy, 1982), 1.38 I/kg in calves (Riond et al, 1989), 1.5 to 3.5 I/kg in dogs (Michel et al, 1979), 2.28 I/kg in cows and ewes (Ziv & Sulman, 1974), 4.5 to 7 I/kg in rats (Michel et al, 1984) and 9.78 I/kg in goats (Jha et al, 1989). The lower value of apparent volume of distribution found in the present study may be attributed to higher plasma protein binding, as well as a lower gut reabsorption of drug in the chicken.…”
Section: Discussioncontrasting
confidence: 79%
“…Doxycycline is highly lipophilic and would be expected to be distributed widely in the chicken. Nevertheless, the V^m*) of 0.28 ± 0.02 I/kg determined in the present study was much lower than that reported for other species: 0.75 I/kg in adult humans (Raghuram & Krishnaswamy, 1982), 1.38 I/kg in calves (Riond et al, 1989), 1.5 to 3.5 I/kg in dogs (Michel et al, 1979), 2.28 I/kg in cows and ewes (Ziv & Sulman, 1974), 4.5 to 7 I/kg in rats (Michel et al, 1984) and 9.78 I/kg in goats (Jha et al, 1989). The lower value of apparent volume of distribution found in the present study may be attributed to higher plasma protein binding, as well as a lower gut reabsorption of drug in the chicken.…”
Section: Discussioncontrasting
confidence: 79%
“…Following a single intravenous administration, a tv2p of 10 h was obtained by graphic determination (Schach von Wittenau & Yeary, 1963), and a harmonic mean of 10.36 h (Wilson et al, 1988) was documented. A t,/:p value of 11.8 h was determined by regression on means of data after a single oral administration (Michel et al, 1979). In dogs, doxycyline tlj2p estimates after a single i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of 10mg/kg doxycycline polyphosphate in gelatine capsules to dogs resulted in peak concentrations (Cma,) of 4.6 pg/ml after 2. 8 h (t,,,,,; Michel et al, 1979). Doxycycline bioavailability after oral administration to cats and dogs has not been determined to date.…”
Section: Discussionmentioning
confidence: 99%
“…Peak serum concentrations of doxycycline and tetracycline occur 2 to 3 h after oral administration. 1 Doxycycline is at least 5-10 times more lipophilic than tetracycline, resulting in higher tissue penetration and a better overall antimicrobial profile than tetracycline. 2 The elimination mechanism for doxycycline differs from most other tetracyclines as it enters the intestine both by both biliary excretion and by diffusion, 3 with 75% excreted by the biliary route and faeces and urinary excretion accounting for the remainder.…”
mentioning
confidence: 99%